How Large Are Global Energy Subsidies? - Coady, David (IMF Working Papers; Working Paper ;, 2015)
This paper provides a comprehensive, updated picture of energy subsidies at the global and regional levels. It focuses on the broad notion of post-tax energy subsidies, which arise when consumer prices are below supply costs plus a tax to reflect environmental damage and an additional tax applied to all consumption goods to raise government revenues. Post-tax energy subsidies are dramatically higher than previously estimated, and are projected to remain high. These subsidies primarily reflect under-pricing from a domestic (rather than global) perspective, so even unilateral price reform is in countries' own interests. The potential fiscal, environmental and welfare impacts of energy subsidy reform are substantial.